Constructal design for blast furnace wall based on the entransy theory. (5th May 2016) - Liu, Xiong; Chen, Lingen; Feng, Huijun; Sun, Fengrui
Highlights: Constructal design of blast furnace wall is conducted. Minimum entransy dissipation rate is taken as an optimization objective. There exist twice optimal axial diameter ratio and cooling water velocity. Optimal cross-section shape of the cooling pipe is near round. Abstract: Based on the entransy dissipation extremum principle for thermal insulation process, constructal design of blast furnace wall is performed in this paper. Optimal construct of the cooling stave in the furnace wall is obtained by using finite element method. The results show that there exists twice optimal axial diameter ratio and optimal cooling water velocity which makes the entransy dissipation rate of the blast furnace wall reach its critical minimum. Moreover, the optimal cross-section shape of the cooling pipe is approximately round. Within the discussed variation range of the axial diameter ratios, the minimum entransy dissipation rate is 2.73% less than the maximum entransy dissipation rate when the cooling water velocity is preset. Within the discussed variation range of the cooling water velocities, the minimum entransy dissipation rate is 2.09% less than the maximum entransy dissipation rate. Besides, increasing inlet temperature of cooling water appropriately is propitious to improve the global thermal insulation performance of the blast furnace wall while it cannot reduce the cooling water. The global thermal insulation performance of the furnace wall with approximately round cooling pipe is higher than that with composite-oblate cooling pipe.